Emerging cool white light emission from Dy3+ doped single phase alkaline earth niobate phosphors for indoor lighting applications. Issue 39 (16th September 2015) - Vishwakarma, Amit K.; Jha, Kaushal; Jayasimhadri, M.; Sivaiah, B.; Gahtori, Bhasker; Haranath, D.
Abstract : Single-phase cool white-light emitting BaNb2 O6 :Dy 3+ phosphors have been synthesized and their structural, luminescence and colorimetric properties have been investigated in detail. Abstract : Single-phase cool white-light emitting BaNb2 O6 :Dy 3+ phosphors have been synthesized via a conventional solid-state reaction method and characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM) observations and spectrofluorophotometric measurements. XRD and Rietveld structural refinement studies confirm that all the samples exhibit pure orthorhombic structure [space group – C 2221 (20)]. SEM observations reveal the dense particle packaging with irregular morphology in a micron range. The as-prepared phosphors exhibit blue (482 nm) and yellow (574 nm) emissions under 349, 364, 386 and 399 nm excitations corresponding to 4 F9/2 → 6 HJ ( J = 15/2, 13/2) transitions of Dy 3+ ions. The energy transfer mechanism between Dy 3+ ions has been studied in detail and the luminescence decay lifetime for the 4 F9/2 level was found to be around 146.07 μs for the optimized phosphor composition. The calculated Commission Internationale de L'Eclairage (CIE) chromaticity coordinates for the optimized phosphor are ( x = 0.322, y = 0.339), which are close to the National Television Standard Committee (NTSC) ( x = 0.310, y = 0.316) coordinates. The values of CIE chromaticity coordinates and correlated color temperature (CCT) of 5907 K endorse cool white-light emission from the phosphor. The study reveals that BaNb2 O6 :Dy 3+ phosphor could be a potential candidate for near ultra-violet (NUV) excited white-LED applications.